PENDIDIKAN KARAKTER PANCASILA DAN INTEGRITAS MAHASISWA DALAM PENCEGAHAN KORUPSI - Utomo, Abiyu Bimo Ridho Ghuno; Widya Gita Tantya; Ayu Diah Putri; Octavia Putri Permata; Kusnul Khotimah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Corruption is a severe issue that affects social inequity, moral deterioration, and the erosion of public confidence in state institutions. A comprehensive strategy is needed to prevent corruption, and character education grounded in Pancasila values is one such strategy. The purpose of this study is to examine how Pancasila-based character education shapes students' integrity and how it helps avoid corruption. A descriptive approach that combines qualitative and quantitative methodologies is the research methodology employed. University students were used as research subjects in surveys, interviews, and literature reviews to gather data. The findings indicate that the majority of students exhibit favorable views toward anti-corruption behavior and have a solid grasp of Pancasila values. The degree of student integrity and the comprehension of Pancasila values are significantly correlated. Character education based on Pancasila has been successful in fostering values like justice, accountability, and honesty, which are the cornerstones of anti-corruption sentiments. However, issues like the effects of globalization and the poor application of values in everyday life continue to be barriers. To create a generation of students who are honest and dedicated to preventing corruption, Pancasila character education must be strengthened in the curriculum and supported by educational institutions and society.